Selective hydrolysis of oxidized insulin chain B by a Zr(iv)-substituted Wells–Dawson polyoxometalate. Issue 4 (12th September 2014) - Sap, Annelies; Absillis, Gregory; Parac-Vogt, Tatjana N.
Abstract : The reactivity of a Zr(iv )-substituted Wells–Dawson POM towards the flexible 30-mer polypeptide, oxidized insulin chain B, was examined. Hydrolysis of the polypeptide has been achieved at physiological pH and temperature in a fast (0.45 h −1 ) and selective manner. Abstract : We report for the first time on the selective hydrolysis of a polypeptide system by a metal-substituted polyoxometalate (POM). Oxidized insulin chain B, a 30 amino acid polypeptide, was selectively cleaved by the Zr(iv )-substituted Wells–Dawson POM, K15 H[Zr(α2 -P2 W17 O61 )2 ]·25H2 O, under physiological pH and temperature conditions in aqueous solution. HPLC-ESI-MS, LC-MS/MS, MALDI-TOF and MALDI-TOF MS/MS data indicate hydrolysis at the Phe1–Val2, Gln4–His5, Leu6–Cys(SO3 H)7, and Gly8–Ser9 peptide bonds. The rate of oxidized insulin chain B hydrolysis (0.45 h −1 at pH 7.0 and 60 °C) was calculated by fitting the integration values of its HPLC-UV signal to a first-order exponential decay function. 1 H NMR measurements show significant line broadening and shifting of the polypeptide resonances upon addition of the Zr(iv )-POM, indicating that interaction between the Zr(iv )-POM and the polypeptide takes place in solution. Circular dichroism (CD) measurements clearly prove that the flexible unfolded nature of the polypeptide was retained in the presence of the Zr(iv )-POM. The thermal stability of the Zr(iv )-POM in the presence of the polypeptide chain during the hydrolytic reaction was confirmed by 31 P NMR spectroscopy. Despite the highly negative charge of the Zr(iv )-POM, the mechanism of interaction appears to be dominated by a strong metal-directed binding between the positively charged Zr(iv ) center and negatively charged amino acid side chains.